KORELASI ASUPAN MAKANAN, STRES, DAN AKTIVITAS FISIK DENGAN HIPERTENSI PADA USIA MENOPAUSE (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2017)
Almost 65% of high blood pressure cases in old women is caused by estrogen deficiency, while 35% can be influenced by lifestyle factors and other factors. This study aimed to analyze lifestyle factors on hypertension at the age of menopause in Tlogosari Wetan Public Health Center of Semarang City. As many as 50 people has used as respondent randomly by cross sectional design study. Analysis of the data in this study using univariate, bivariate using Spearman rank test, and multivariate analysis using logistic regression test. The results in this study are there was a significant relationship between physical activity, stress , fat intake, the intake of sodium (p<0,05) against hypertension at the age of menopause. The results of logistic regression showed that sodium intake have a higher level of risk to hypertension (0.021). It can be concluded that food choice, stress, and physical activity are the lifestyle factors that contribute significantly to the risk of hypertension in menopause women.